Sistema de devolución del crédito tributario IVA y su impacto en la liquidez de la empresa Exp. e Imp. Manobal cantón Quevedo periodo 2022-2023 - Icaza Peralta, Joyce Michelle (2024)
The objective of the present research is to know the impact of the VAT tax credit refund process on the liquidity of the company "Exp. E Imp. Manobal" during the period from 2019 to 2022, where there is an optimal VAT recovery process that allows reaching higher levels of operational and financial competitiveness. The present research allowed detecting the factors that influence the realization of the tax credit claim process. The universe of the study was centered on the comparison of current liquidity and on an interview with the general accountant and tax assistant of said entity. The deductive and inductive methods were used, in addition to external bibliographic sources that allowed the adequate collection of data. The results obtained showed that the company has difficulties in the collection of documentation and information necessary for the VAT reclaim process. Due to the implementation of the mango component in the year 2022, the tax credit and VAT recovered presented a development of ($801,415.97) and ($605,686.51), therefore, liquidity also rose 1.64% in that year, this on the basis of the tests that were implemented. In addition, it was found that the tax update is key for the proper execution of the VAT refund procedure, the evolution of the tax credit will depend on the new acquisitions made for production, thus, the dematerialized credit notes for the recovered VAT are a very useful tool for the payment of short-term obligations